The role of salience in metaphorical processing in English as a Foreign Language - Stanojević, Mateusz-Milan; Ljubičić, Mateja (2012)
Psycholinguistic evidence suggests that salience and conventionality play a crucial role in processing conceptual metaphors (cf. e.g. Gentner and Bowdle 2008 ; Giora 1997). Still, this has not been explicitly connected with corpus studies, although it would seem to be a valid way of cross-fertilization (cf. Steen 2007). Moreover, despite a number of studies of the role of metaphor in classroom discourse (Cameron 2003) and language learning (Boers 2000), little is known about the effects of metaphor processing in the second language (but cf. Littlemore 2010). In this paper we study metaphorical processing in English as a Foreign Language (EFL), in combination with a corpus study. The overall aim is to show that it is salience (Giora 1997) rather than metaphoricity that plays a crucial role in this respect. First, we conducted a picture priming task (cf. Valenzuela and Soriano (2007) with 42 EFL speakers testing the salience of target words anger, fury, wrath and rage in the conceptual metaphor anger is a hot fluid in a container. The results show that the effects of priming were overridden by salience: reaction times were faster for anger than for wrath regardless of the unrelated prime in the former. In the corpus study done using COCA (http://corpus.byu.edu/coca/), we checked for differences in frequency and potentially metaphorical collocations (Stefanowitsch 2004 ; Stanojević 2009). The results confirm the expected differences in frequency between the four words (anger being the most and wrath the least frequent one), and the differences in the type and quality of potential metaphors used with the four words (anger having most characteristic metaphors, and wrath least). This suggests a greater salience of anger, which ties in with the priming task results. Overall, this may mean that the processes in L1 and L2 correspond when it comes to conceptual metaphor processing. Boers, Frank. 2000. “Metaphor Awareness and Vocabulary Retention.” Applied Linguistics 21 (4): 553–571. Cameron, Lynne. 2003. Metaphor in Educational Discourse. London: Continuum. Gentner, Dedre, i Brian F. Bowdle. 2008. “Metaphor as Structure-mapping.” U The Cambridge Handbook of Metaphor and Thought, ur. Raymond W. Gibbs, 109–128. New York: Cambridge University Press. Giora, Rachel. 1997. “Understanding Figurative and Literal Language: The Graded Salience Hypothesis.” Cognitive Linguistics 8 (3): 183–206. Littlemore, Jeanette. 2010. “Metaphoric Competence in the First and Second Language: Similarities and Differences.” U Cognitive Processing in Second Language Acquisition: Inside the Learner’s Mind, ur. Martin Pütz i Laura Sicola, 295–316. Amsterdam, Philadelphia: John Benjamins Publishing Company. Stanojević, Mateusz-Milan. 2009. “Dijakronijska varijacija u metaforičkim modelima: razrada metodologije”. Doktorska disertacija, Sveučilište u Zadru. Steen, Gerard. 2007. Finding Metaphor in Grammar and Usage. Amsterdam, Philadelphia: John Benjamins Publishing Co. Stefanowitsch, Anatol. 2004. “Happiness in English and German: A Metaphorical-pattern Analysis.” U Language, Culture, and Mind, ur. Michel Achard and Suzanne Kemmer, 137–149. Stanford: Center for the Study of Language and Information. Valenzuela, Javier, i Cristina Soriano. 2007. “Looking at Metaphors: a Picture-word Priming Task as a Test for the Existence of Conceptual Metaphor.” Barcelona English Language and Literature Studies (16). http://www.publicacions.ub.edu/revistes/ bells16/documentos/articles_05.pdf.
Projekt MZOS
ENG